The Effect of Individual Characteristics, Service Compensation and Work Ethics on Generation Y of Nursing Performance (Global Journal of Management and Business Research, 2019)
This study aimed to examine the effect of individual characteristics, compensation for services and work ethic on the performance of the nurses at the General Hospital of the City of Mataram. This study uses a quantitative approach and included in the associative causal research. The study population was all nurses on duty at the Hospital as many as 318 people. Based on the calculation formula Slovin, then the size of the sample used in this study as many as 178 people. Therefore, in this study population is homogeneous, then the sample is determined by a simple random sampling technique. Data were collected using a questionnaire distributed to 178 respondents. Furthermore, the data were analyzed using multiple linear regression. The results showed that the characteristics of the individual, compensation services and work ethic partial and simultaneous significant positive effect on the performance of nurses. Compensation services are the dominant variable affecting the performance of the nurses at the Hospital. It is advisable for the management of the Hospital to give priority to members who excel by providing continuing education, training, and career development.
Keywords: individual characteristics; compensation; work ethic; performance